Об одном подходе к дискретизации метода М. М. Лаврентьева - Солодкий, С.Г. (Український математичний журнал, 1996)
We propose a new scheme of discretization of the Lavrent’ev method for operator equations of the first kind with self-adjoint nonnegative operators of certain “smoothness.” This scheme is more economical in the sense of the amount of used discrete information as compared with traditional approaches.